Antártica, un continente para el tercer milenio - Pinochet de la Barra, Oscar (Universidad de Chile. Instituto de Estudios Internacionales, 1990)
Antarctica is a continent where geography arrived millions of years ago, but where history is, only today, witnessing the first human events. There they rehearse what this planet could be in the third millennium. At the southern end of the earth, a form of international relationship is being tested, a way of life, with a high ethical content based on understanding and mutual help, which could well be extended tomorrow, little by little, to the other continents. The global concern for the white continent should inspire a similar attitude for the rest of the planet; however, the potential use of its natural resources emerges as the bone of contention, where ecological consciousness is confronted with the search for economic exploitation. Antártica es un continente donde la geografía llegó hace millones de años, pero donde la historia está, solo hoy, desgranando los primeros acontecimientos humanos. Allí se ensaya lo que podría ser este planeta en el tercer milenio. En el extremo austral de la tierra se está ensayando una forma de relación internacional, una forma de vida, de alto contenido ético basada en el entendimiento, en la comprensión, en la ayuda mutua, que bien podría extenderse mañana, poco a poco, a los demás continentes. La preocupación mundial por el continente blanco debiera inspirar una actitud semejante para el resto del planeta, sin embargo, el potencial aprovechamiento de sus recursos naturales surge como la manzana de la discordia, donde se enfrentan la conciencia ecológica con la búsqueda de una explotación económica.